2008
DOI: 10.1183/09031936.00099507
|View full text |Cite
|
Sign up to set email alerts
|

Metallic stent and flexible bronchoscopy without fluoroscopy for acute respiratory failure

Abstract: Stent implantation has been reported to facilitate liberation from mechanical ventilation in patients with respiratory failure due to central airway disease. The present retrospective cohort study sought to evaluate the risk and benefit of stent implantation via bronchoscopy without fluoroscopic guidance in mechanically ventilated patients.From July 2001 to September 2006, 26 patients with acute respiratory failure were recruited. A bronchoscope was inserted through a mouth guard into the space between the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
1
39
1
Order By: Relevance
“…Will the patient receive sufficient ventilation? The results of the previous research [10] and the present study all showed that patients received enough oxygen support during the operation.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Will the patient receive sufficient ventilation? The results of the previous research [10] and the present study all showed that patients received enough oxygen support during the operation.…”
supporting
confidence: 53%
“…Winding through an airway outside a tracheal tube needs more skill and time. It might be an important reason that the operation time of the present study was less than that of the previous study [10] . In addition, an ultrathin bronchoscope with an outer diameter of about 1.8-2.8 mm may be inserted simultaneously with a delivery catheter into a tracheal tube to implant a metallic stent.…”
contrasting
confidence: 50%
See 3 more Smart Citations